Using social media to support teaching and learning in higher education: an analysis of personal narratives - Kara, Nurten; Cubukcuoglu, Begum; Elci, Alev (Assoc Learning Technology-Alt, 2020)
The increasing trend of using new media technologies and particularly social media (SM) among students provides an advantage for lecturers. Apparently their importance accelerated with the application of social distancing during a pandemic crisis such as the one World has been experiencing since the end of 2019. In this article, the stories of two academics are used expressing experiences, motives and perceptions on benefits and challenges of using SM to support teaching and learning in the classroom. The stories which form the data of the research describe how and why the participants started to use SM, their intended purpose and the ways of use. Besides, reasons, difficulties and positive as well as the negative sides are explored. The findings show that the virtual learning environments provided by SM facilitated the development of students' enthusiasm and interaction with peers assertively, thus increasing the students' participation. Because of emerging technologies, SM platforms surge and plummet quickly; therefore, it is important for institutions to either develop their platform or to subscribe to existing ones for effective knowledge sharing at an institutional level with clear ethical rules.
Keywords: new media; narrative research; storytelling; knowledge sharing; ethical use of social media